PENERAPAN MEDIA LOOSE PARTS UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG DAN MENGENAL KONSEP BILANGAN PADA ANAK KELOMPOK A DI RA BINA AMANAH (UNISMA, 2020)
This research was conducted to determine the ability to count and recognize the concept of numbers through the media of loose parts in A RA Bina Amanah group children. This research is based on the results obtained from the researchers' initial observations through interviews with classroom educators and the results of this study state that the ability to calculate and recognize the concept of group A children is lacking. Media that is used by educators only uses child worksheets only. This research was conducted on group A children in RA Bina Amanah Kota Batu with a total of twenty-four students. Data collection techniques used were observation, interviews and documentation. The results showed that the application of loose parts media could improve the ability to count and recognize the concept of group A RA Bina Amanah numbers before the study only reached an average percentage of 33.33%. After conducting research with the application of loose parts media the ability to calculate and recognize the concept of numbers in the first cycle reached an average percentage of 54.17% and the second cycle increased by 91.67%. Completion percentage reached